Estimation of pubertal growth using Hand-Wrist radiographs and Orthopantomographs (prospective study) (Mustansiria Dental Journal, 2018)
The present study tried to verify the most familiar method to orthodontist forpubertal stage estimation which is very important in orthodontic diagnosis and plan byusing Hand – Wrist radiographs and Orthopantomography (OPG). The sample of thisstudy has been selected from patients who were attending the Orthodontic departmentand Pedodontic and Preventive Dentistry department at the College of Dentistry –Baghdad University. Before starting the study a legal approval was obtained and theobjective of the study was explained to the parents of each participant. The sampleconsisted of 90 subjects (45 females and 45 males), of certain criteria, between 10 and16 years of age. The subjects of the sample were of Iraqi Arab origin; the radiographswere interpreted by specialist radiologist. Developmental stage of mandibular left 2ndmolar show a higher correlation with skeletal maturation stage of hand and wristbones (r=0.9) than the canine (r=0.7) for both males and females and can beconsidered as reliable indicator for maturational stage of individual. The skeletal ageis matched the chronological age at the pubertal growth spurt approximately 12 yearsfor females and 14 years for males, and then the sample had a tendency towardsadvanced maturation with mean skeletal age of the participating subjects being greaterthan the chronological age at the maturity stages. Developmental stage of mandibularleft 2nd molar might be considered as reliable indicator for maturational stage ofindividual, For the sample of this study, the skeletal age is matched the chronologicalage at the pubertal growth spurt approximately 12 years for females and 14 years formales.